Identifikasi Daerah Rawan Longsor Berbasis SIG di Kecamatan Sumowono - Kareza Ahmad; Imam Buchori (Teknik PWK (Perencanaan Wilayah Kota), 2019)
One of the natural disasters that often occur in hilly areas is landslides. Landslides can occur due to the movement of masses of land, rocks, the intensity of very high rainfall, and many other factors, and have the potential to damage the environment by causing various losses. Sumowono District is one of the vulnerable areas to landslides in Kabupaten Semarang, which is located in highland and mountainous areas with the soil condition that are quite vulnerable with high intensity of rainfall. Landslides often occur in Sumowono District and cause losses. In 2015, there were around 12 landslides in this sub-district and some affected residents and caused material losses. Distribution of landslides and the time when the disaster occurred was difficult to predict, so there was no effort early treatment before the landslide disaster occurs. The purpose of this study is mapping and identifying the distribution of vulnerable areas to landslides using matrix matrix pairwise comparison method and SNI Permen PU No.22/PRT/M/2007 in Sumowono District. The methods that will be used in this study are the scoring method, matrix pairwise comparison in the context of AHP with expert judgment, and weighted overlay technique. Criteria used include topography, soil type, geological structure, rainfall, land cover, and population density. The results of this study are the distribution of landslide vulnerable areas based on SNI Permen PU No.22/PRT/M/ 2007 with modification and pairwise comparison. Identification of the distribution of landslide areas that are more accurate in representing condition in the area is SNI Permen PU that are classified into three classes, which is high vulnerability with an area of 1.089,07 Ha or 18,53% spread across 16 villages, with an area of 3.513,64 ha or 59,77% spread over 16 villages, and low with an area of 1.276,20 Ha or 21,71% spread over 15 villages.